Imagination and Science in Romanticism - Sha, Richard C. (Book collections on Project MUSE., 2018)
"In Imagination and Science in Romanticism, Richard Sha challenges the idea that the imagination could only be applied to the literary and that its primary role was to transcend scientific concerns. Sha shows how the imagination functioned within physics and chemistry in Prometheus Unbound, neurology in Blake's Four Zoas, physiology in Coleridge's Biographia Literaria, and obstetrics and embryology in Frankenstein. Sha also shows how the imagination was used in the scientific community, highlighting as primary examples the work of Davy, Faraday, Priestley, Kant, Mary Somerville, Oersted, Marcet, Swedenborg, Blumenbach, Buffon, Erasmus Darwin, and Von Baer, among others. Both fields profited from thinking about how the imagination could cooperate with reason and how hypotheses that had the possibility of actuality could benefit their work"--